Kunst in België na 1975 - Bex, Florent; Baudson, Michel; De Deyne, Lieve; Draguet, Michel; Hoet, Jan (Antwerpen : Mercatorfonds, 2001)
van Oost, Jan ; Vercruysse, Jan ; Van Snick, Philippe ; Charlier, Jacques ; de Cordier, Thierry ; De Beul, Bert ; Muyle, Johan ; Eerdekens, Fred ; Vermeiren, Didier ; Swennen, Walter ; Rogiers, Peter ; De Vylder, Paul ; Van Bossche, Guy ; De Bruyckere, Berlinde ; Delvoye, Wim ; Huyghe, Philip ; Denmark ; De Smet, Gery ; Cole, Willem ; Vandevelde, Ludwig ; Geys, Jef ; Pacquée, Ria ; Deleu, Luc ; Bijl, Guillaume ; Rombouts, Guy ; Droste, Monika ; De Bruyn, Goele ; Duchateau, Hugo ; Lohaus, Bernd ; Dujourie, Lili ; Copers, Leo ; Mistiaen, Carlo ; Van Caeckenbergh, Patrick ; François, Michel ; Castelyns, Frank ; Buggenhout, Peter ; Devos, Danny ; Corillon, Patrick ; Lizene, Jacques ; Maeyer, Marcel ; De Vos, Dirk ; Heyrman, Hugo (Dr. Hugo Heyrman) ; Lennep, Jacques ; Swennen, Walter ; Bervoets, Fred ; Roobjee, Pjeroo ; Tuymans, Luc ; Vanderleenen, Marc ; Vermeiren, Florent ; de Vos, Eddy ; Cruyt, Laurent ; Bytebier, Jean-Marie ; Delrue, Ronny ; Chapelle, Chantal ; De Blieck, Marc ; Voordeckers, Jürgen ; Broucke, Koen ; Van Imschoot, Jan ; Geyskens, Vincent ; Fabre, Jan ; Van Isacker, Philip ; van Oost, Jan ; Rogiers, Peter ; Vertessen, Liliane ; Pacquée, Ria ; Van Kerckhoven, Anne-Mie ; Bijl, Guillaume ; Grimonprez, Johan ; Vandenberg, Philippe ; Lennep, Jacques ; Dewaele, Daniel ; Jano ; Bisschop, Geert ; Denmark ; Wesselli, Wessel Di ; Verschueren, Bob ; Queeckers, Bernard ; Vergara Santiago, Angel ; Crabeels, Cel ; Eerdekens, Fred ; Francis, Filip ; Corillon, Patrick ; Bruna-Hautman, Sigefride ; Nyst, Jacques-Louis ; de Mey, Gaston ; Sack, Dorry ; d'Oultremont, Juan ; Octave, Jean-François ; Mistiaen, Carlo ; Tordoir, Narcisse ; Broodthaers, Marcel ; Braeckman, Dirk ; Kasimir, Marin ; Daems, Anne ; Kempenaers, Jan ; Boon, Elke ; François, Michel ; etc.
boek